A computer‐aided approach for designing dielectric‐covered planar array antennas consisting of longitudinal slots. Issue 3 (18th November 2018) - Moradian, Mahdi
Abstract: A straightforward design approach is proposed to design arrays of longitudinal slots covered with dielectric slabs. The design of the arrays is accomplished via linking the slotted array antennas fed by the waveguides to a corresponding array of the loaded slots cut in an infinite ground plane and covered with dielectric slab. In this regard, the Elliott's design equations are modified for the dielectric‐covered longitudinal slotted array antennas. The introduced design equations are employed to find the final dimensions of the slot antennas while the updated mutual admittances of the corresponding array of the loaded slots are used iteratively in the design equations. Employing the introduced design equations, a two by three slotted array antenna was designed, simulated and tested. The proposed design approach is verified by the simulation and the measurement results.